INNOVATION IN ISLAMIC RELIGIOUS EDUCATION LEARNING AT MADRASAH ALIYAH NURUL JIHAD BULAGI - Kasmiati Kasmiati; Oyan D. Taufiq; Marwany Marwany (Prodi PAI Sekolah Tinggi Agama Islam Serdang Lubuk Pakam, 2025)
Innovation in Islamic Religious Education learning in madrasahs must always be carried out. Through this innovation, Islamic Religious Education in madrasahs can be taught effectively in distributing Islamic knowledge and character to students. For this reason, this study aims to identify and explain innovations in Islamic Religious Education learning at Madrasah Aliyah Nurul Jihad Bulagi. The research method used is a qualitative paradigm with an emphasis on field research. Data collection techniques are carried out through observation, interviews, and documentation, while data analysis techniques use data reduction, data presentation, and data verification. The results of the study show that first, the implementation of Islamic Religious Education learning is carried out using the discovery and inquiry methods. Second, learning innovations can increase student involvement to be active in the learning process. Third, innovations in Islamic Religious Education learning are able to build positive responses and deep impressions of students towards Islamic Religious Education subject matter.